Specificity of root microbiomes in native‐grown Nicotiana attenuata and plant responses to UVB increase Deinococcus colonization. Issue 9 (8th March 2017) - Santhanam, Rakesh; Oh, Youngjoo; Kumar, Ramesh; Weinhold, Arne; Luu, Van Thi; Groten, Karin; Baldwin, Ian T.
Abstract: Plants recruit microbial communities from the soil in which they germinate. Our understanding of the recruitment process and the factors affecting it is still limited for most microbial taxa. We analysed several factors potentially affecting root microbiome structure – the importance of geographic location of natural populations, the microbiome of native seeds as putative source of colonization and the effect of a plant's response to UVB exposure on root colonization of highly abundant species. The microbiome of Nicotiana attenuata seeds was determined by a culture‐dependent and culture‐independent approach, and the root microbiome of natural N. attenuata populations from five different locations was analysed using 454‐pyrosequencing. To specifically address the influence of UVB light on root colonization by Deinococcus, a genus abundant and consistently present in N. attenuata roots, transgenic lines impaired in UVB perception (ir UVR8 ) and response (ir CHAL ) were investigated in a microcosm experiment with/without UVB supplementation using a synthetic bacterial community. The seed microbiome analysis indicated that N. attenuata seeds are sterile. Alpha and beta diversities of native root bacterial communities differed significantly between soil and root, while location had only a significant effect on the fungal but not the bacterial root communities. With UVB supplementation, root colonization of Deinococcus increased in wild type, but decreased in irUVR8 and irCHAL plants compared to nontreated plants. Our results suggest that N. attenuata recruits a core root microbiome exclusively from soil, with fungal root colonization being less selective than bacterial colonization. Root colonization by Deinococcus depends on the plant's response to UVB.